2017
DOI: 10.1177/0739986317717719
|View full text |Cite
|
Sign up to set email alerts
|

Do Independent Women Participate in Demonstrations More? Empowerment and Politics in Predicting Activism Among Mexican Women

Abstract: The influence of Latinos on all aspects of the American political landscape has increased dramatically in recent years. However, research on political participation among Latinas has been scarce. This study examined the factors influencing participation in protests, a type of nonelectoral political behavior, among Mexican women. This research was based on surveys with 290 Mexican women from the Chicago area and explored the role of their levels of economic, social, and household empowerment in explaining parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Table 3a represents the 10 most frequently sampled states with Texas, California Arizona again leading the list. While Illinois is adequately represented here, due to the strong influence from Julia Albarracin’s work making up four out of the 5.25 articles in Illinois (see Albarracin et al, 2017 for an example). New York is not among the top 10 despite its large Latinx population.…”
Section: Resultsmentioning
confidence: 99%
“…Table 3a represents the 10 most frequently sampled states with Texas, California Arizona again leading the list. While Illinois is adequately represented here, due to the strong influence from Julia Albarracin’s work making up four out of the 5.25 articles in Illinois (see Albarracin et al, 2017 for an example). New York is not among the top 10 despite its large Latinx population.…”
Section: Resultsmentioning
confidence: 99%
“…In Mexico, female participation in demonstrations as a form of claims making is high, although only among women who are free from domestic restrictions laid down by their husbands and free from house chores (Albarracin, Munier and Bail 2017).…”
Section: Women's Civic Participationmentioning
confidence: 99%
“…Mlambo, Kapingura, and Meissner's ( 2019) study of the South African Development Commission region also demonstrated the connection between women's political participation and their involvement in the labour force. In Latin America as well, participation in paid employment and control over one's income were found to have some degree of influence on Mexican women's political participation (Albarracin et al 2017).…”
Section: Employment and Incomementioning
confidence: 99%
“…Diverse racial coalitions may also help increase the political participation of people of color and immigrants. Research shows that some immigrants turn toward their own ethnic group when facing discrimination or when they experience low trust toward the government (Albarracin et al 2017; Michelson 2003). A diverse coalition may placate fears that political actors would ignore the concerns of one's group.…”
Section: Literature Reviewmentioning
confidence: 99%